A fuzzy uncertainty model for analytical and numerical homogenization of transversely fiber reinforced plastics - Caylak, Ismail; Penner, Eduard; Mahnken, Rolf (PAMM)

Model adaptivity on mean‐field and full‐field homogenization methods considering hierarchical unit cells - Ju, Xiaozhe; Mahnken, Rolf (PAMM)

Damage simulation of fiber reinforced composites using mean‐field homogenization methods - Lenz, Peter; Mahnken, Rolf (PAMM)

Lehrbuch der Technischen Mechanik - Band 2: Elastostatik - Mahnken, Rolf

Adaptive Finite Element Methods for Direct and Inverse Problems in Nonlinear Solid Mechanics - Widany, Kai-Uwe

Experimental Characterization and Constitutive Modeling of Reinforced Thermoplastic and Thermosetting Polymers - Damman, Christian

Adaptive Methods in the Mechanics of Heterogeneous Materials - Ju, Xiaozhe

A multi-mechanism model for cutting simulations combining asymmetric effects and gradient phase transformations - Cheng, Chun

„A coupled phase field/diffusion model for upper and lower bainitic transformation” - Düsing, M.; Mahnken, R. (International Journal of Solids and Structures)
Bainite is a steel microstructure consisting of three phases, bainitic ferrite, austenite and carbides. It forms in two different morphologies, upper and lower bainite, where different diffusion mechanisms are dominant. The aim of this work is to simulate both transformations within a unified model. To this end, we extend an own previously published model for lower bainite with diffusion across the phase interface. As a central idea we introduce weighted Helmholtz energy functions and a weighted mobility tensor, respectively. The individual Helmholtz energy functions and mobility terms are related to the different diffusion mechanisms which are responsible for the formation of both morphologies. Two representative examples illustrate the capability of the coupled phase field/diffusion model and show the expected behaviour.
Keywords: Coupled phase field/diffusion model; Bainite; Multiphase field method; Cahn–Hilliard diffusion; Diffusion across the interface; Lower bainitic transformation; Upper bainitic transformation; Thermodynamic framework; Microforce balance

"A least squares approach for effective shear properties in an n-layered sphere model" - Mahnken, Rolf; Lenz, Peter; Dammann, Christian (Archive of Applied Mechanics)

"Sequential biaxial stretching of polycarbonate-films for characterization of strain-induced anisotropy" - Dammann, Christian; Caylak, Ismail; Mahnken, Rolf (GAMM-Mitteilungen)

A multivariate stochastic material model with correlated material parameters - Penner, Eduard; Caylak, Ismail; Mahnken, Rolf (PAMM)

"Error-controlled homogenization for a class of linear elastic composite problems" - Ju, Xiaozhe; Mahnken, Rolf (PAMM)

"A coupled phase transformation and solute diffusion model for bainitic transformation" - Düsing, Martin; Mahnken, Rolf (PAMM)

"A fuzzy finite element method for sparse experimental data based on a possibilistic approach" - Dridger, Alex; Caylak, Ismail; Mahnken, Rolf (PAMM)

"Goal-oriented adaptivity for parameter identification in linear micromorphic elasticity" - Ju, Xiaozhe; Mahnken, Rolf (PAMM)

Goal-oriented adaptivity for linear elastic micromorphic continua based on primal and adjoint consistency analysis - Ju, X.; Mahnken, R. (International Journal for Numerical Methods in Engineering)

"Stochastic hyperelastic modeling considering dependency of material parameters" - Caylak, I.; Dridger, A.; Mahnken, R. (Computational Mechanics)

„Goal-oriented adaptivity on mean-field and full-field homogenization methods with a view to hierarchical unit cells“ - Ju, X.; Mahnken, R. (31st International Workshop on Research in Mechnanics of Composite)

„On the connection between possibility theory and probability box theory in structural mechanics“ - Dridger, A.; Caylak, I.; Mahnken, R.; Penner, E. (13th World Congress in Computational Mechanics)